160k views
2 votes
What is 3(x - 1) = 2x + 9

2 Answers

2 votes

Answer:

x=12

Explanation:

3(x-1)=2x+9 - Original equation

3x-3=2x+9 - Distribute 3 through the parentheses

3x-2x-3=9 - Move variable to the left-hand side and change sign

3x-2x=9+3 - Move constant to the right-hand side and change its sign

x=9+3 - Collect like terms and add

x=12 - Answer

Hope this helps

User GAURAV KUMAR GUPTA
by
5.0k points
3 votes

Answer:

x=12

Explanation:

Distribute:

3x - 3 = 2x + 9

Combine like terms to one side:

x = 12

User Ikhsan
by
5.1k points